Risk Factors and Morphological Differences of Ruptured Saccular Aneurysm in Different Sites of Anterior Circulation in Patients Presenting with Subarachnoid Haemorrhage (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: All sites of intracranial aneurysms have always been considered together in most of the studies of risk factors of aneurysm rupture. Therefore, it is not known whether some risk factors predispose to aneurysm rupture at a particular location. Morphologies also vary in accordance to different sites of the aneurysm.Objective: The purpose of the present study was to observe the differences in the risk factors, the size, aspect ratio and size ratio among the anterior circulation aneurysms.Methodology: This hospital based cross-sectional study carried out in the Department of Neurology at Dhaka Medical College Hospital (DMCH), Dhaka during July 2013 to June 2015 for a period of two (02) years. Patients with subarachnoid haemorrhage caused by ruptured anterior circulation saccular aneurysms admitted in the Departments of Neurology, Internal Medicine and Neurosurgery Departments at Dhaka Medical College Hospital (DMCH), Dhaka and the Department of Neurointervention at National Institute of Neurosciences and Hospital, Dhaka were enrolled in this study. Patients’ ≥18 years of age with subarachnoid haemorrhage caused by anterior circulation aneurysm which was confirmed by computed tomogram (CT-scan) and/or CSF study and digital subtraction angiography were included in this study. The risk factors were identified by interviewing the patients and the morphology were measured from the digital subtraction angiogram.Results: A total number of 85 patients with ruptured saccular anterior circulation aneurysm were enrolled in this study. In this study anterior communicating artery aneurysm (ACom) was the most frequent site of aneurysm (42%). The mean age of the patients with ACom aneurysm (51.72 ± 9.26 years) was significantly higher than posterior communicating artery (47.5 ± 8.2 years) aneurysm and middle cerebral artery (MCA) (43.41 ± 8.0 years) aneurysm. Above the age of 50 ACom aneurysm was the most frequent aneurysm (OR 5.5, p10 mm was also higher among the middle cerebral artery (35.6%) aneurysms. The size ratio was significantly higher in ACom (3.08±1.23) and MCA (3.04±0.97) aneurysm. ACom (76.4%) and MCA (83.3%) had also more frequent high risk size ratio.Conclusion: In conclusion anterior circulation aneurysms differ in respects of risk factors and morphology.Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 21-28